Interdigital capacitor design for MMIC applications - Conti, Josine Marie C.; Macoy, Meryll O. (2008.)
GaAs MMIC technology has played a vital role in highly developed applications particularly in low noise, high frequency circuits. In designing these circuits, determining the characteristics and behavior of both the passive and active devices used is essential. This study focuses on the design of interdigital microwave capacitors for gallium arsenide MMIC applications. It investigates the effects of varying the capacitor geometry and material properties on the quality factor, capacitance values and operating frequency range. Experimental simulations are conducted for the realization of the passive capacitor.
Undergraduate Student Project (B.S. ECE)--University of the Philippines, Diliman.
Keywords: Microwave integrated circuits; Capacitors -- Design and construction; Microwave capacitor; GaAs MMIC